PENGARUH STORE ATMOSPHERE, PRODUCT QUALITY DAN SERVICE QUALITY TERHADAP BUYING DECISION PADA NIKALUA COFFEE AND EATERY DI BANGSRI JEPARA - Muhammad Deny Setiawan; Nurul Huda (Jurnal Bina Bangsa Ekonomika, 2024)
This study aims to analyze the influence of the variables Store Atmosphere (X1), Product Quality (X2), and Service Quality (X3) on the dependent variables of Buying Decision (Y) of Nikalua Coffee and Eatery Bangsri Jepara café consumers. The respondents to the study were consumers who made purchases at Nikalua Coffee and Eatery Bangsri Jepara café totaling 100 respondents. This study uses primary data by collecting data through observation with questionnaires. The data collection medology uses a survey using the accidental sampling method. The results of the multiple liner regression analysis had a positive relationship between the independent variable and the dependent variable. The result of the determination coefficient with an R square value of 91%, meaning that the model in this study can be explained by 91%, while the remaining 9% is explained by other variables outside the research model